INNOVATIONS IN EDUCATION, DIGITAL TRANSFORMATION, AND PEDAGOGICAL TECHNOLOGIES - Kosimov , Abdulkhay; Makhammadaliyeva, Marvabonu (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article examines the role of innovations, digital transformation, and modern pedagogical technologies in improving educational effectiveness within higher education environments. The rapid development of information and communication technologies, artificial intelligence, cloud computing, and digital learning platforms has significantly transformed traditional educational systems and created new opportunities for interactive, flexible, and learner-centered education. The study focuses on the influence of digital educational tools on learner engagement, accessibility, communication, and academic performance. Special attention is given to the integration of artificial intelligence technologies such as ChatGPT, adaptive learning systems, intelligent tutoring platforms, and AI-supported assessment tools in educational processes. The research employed a quantitative methodology involving 120 participants, including university students and teachers who actively use digital educational technologies. Data were collected through an online questionnaire consisting of 15 Likert-scale questions related to digital literacy, pedagogical innovation, learner motivation, educational accessibility, and challenges associated with technological integration. The collected data were analyzed using descriptive statistical methods. The findings demonstrate that the majority of participants positively evaluate digital transformation in education. Respondents emphasized that online learning platforms, multimedia technologies, virtual communication systems, and AI-assisted educational tools improve access to educational resources, increase flexibility, support independent learning, and enhance classroom interaction. The results also indicate that artificial intelligence contributes to personalized learning experiences, faster feedback, and improved academic support. At the same time, the study identifies several important challenges, including insufficient digital infrastructure, unequal access to technology, ethical concerns, academic dishonesty, and limited digital competence among some educators and learners. The article concludes that digital transformation should be viewed not only as a technological change but also as a pedagogical and organizational process requiring balanced integration of technology and human-centered educational values. Effective implementation of educational innovation depends on institutional support, professional development, digital literacy programs, and ethical regulation of artificial intelligence technologies. The study highlights the importance of maintaining the role of teachers as facilitators, mentors, and ethical guides within increasingly digital learning environments.